2013
DOI: 10.1124/jpet.113.204792
|View full text |Cite
|
Sign up to set email alerts
|

PA21, a New Iron-Based Noncalcium Phosphate Binder, Prevents Vascular Calcification in Chronic Renal Failure Rats

Abstract: Chronic renal failure (CRF) is associated with the development of secondary hyperparathyroidism and vascular calcifications. We evaluated the efficacy of PA21, a new iron-based noncalcium phosphate binder, in controlling phosphocalcic disorders and preventing vascular calcifications in uremic rats. Rats with adeninediet-induced CRF were randomized to receive either PA21 0.5, 1.5, or 5% or CaCO 3 3% in the diet for 4 weeks, and were compared with uremic and nonuremic control groups. After 4 weeks of phosphate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 54 publications
(56 reference statements)
3
57
0
1
Order By: Relevance
“…Zou et al reported results that were in line with those reported in the current study, indicating that the levels of BUN and SCr were higher in patients with CRF [17]. Elevated serum phosphorus levels were observed among rats with CRF [18], and decreased calcium release was also detected in CRF patients [19]. BPS, a new, stable, orally active PGI2 analogue, possesses antiplatelet and vasodilating properties [20].…”
Section: Discussionsupporting
confidence: 88%
“…Zou et al reported results that were in line with those reported in the current study, indicating that the levels of BUN and SCr were higher in patients with CRF [17]. Elevated serum phosphorus levels were observed among rats with CRF [18], and decreased calcium release was also detected in CRF patients [19]. BPS, a new, stable, orally active PGI2 analogue, possesses antiplatelet and vasodilating properties [20].…”
Section: Discussionsupporting
confidence: 88%
“…Administration of SO up to 2 years was associated with only modest increases in tissue iron [28]. An adenine-diet-induced rat model of chronic renal failure assessed the effects of SO on vascular calcification [29]. Lowest vascular calcification scores and FGF-23 concentrations were reported in rats receiving PA21 5% in the diet.…”
Section: Preclinical Data and Animal Studiesmentioning
confidence: 99%
“…The amelioration of hyperphosphatemia and other complications by regulating Pi with Pi binders was demonstrated in several preclinical studies with rodent kidney disease models, such as the adenine model [8][9][10]. Moreover, studies in anti-GBM nephritis [11] or chronic antiThy1 nephritis rat models [12] show that lowering serum Pi with Pi binders or restricted Pi intake improves not only abnormal mineral metabolism but also the progression of kidney disease itself.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies showed the renoprotective effects of Pi regulation in glomerular injury models, little has been reported on the effect of Pi regulation in cases of direct tubular injury. The adenine model commonly used for rat and mouse studies primarily uses tubular injury to induce hyperphosphatemia [8][9][10], but this method is too artificial for evaluating the renoprotective effects of Pi regulation. Because there are only a few studies on hyperphosphatemia induced by glomerular injury, the renoprotective effect of Pi regulation in mice remains unexplored [13].…”
Section: Introductionmentioning
confidence: 99%